Utilization of Salvage and Systemic Therapies for Recurrent Prostate Cancer as a Result of 18F-DCFPyL PET/CT Restaging - Wei Liu, MD; Katherine Zukotynski, MD, PhD, FRCPC; Louise Emmett, MD, FRACP; Hans T. Chung, MD, FRCPC; Peter Chung, MD, FRCPC; Robert Wolfson, MD, FRCPC; Irina Rachinsky, MD, MSc, FRCPC; Anil Kapoor, MD, FRCSC; Ur Metser, MD, FRCPC; Andrew Loblaw, MD, MSc, FRCPC; Gerard Morton, MB, FRCPC; Tracy Sexton, MD, PhD, FRCPC; et al. (Advances in Radiation Oncology, 2021)
Purpose: Our purpose was to investigate the effect of the addition of prostate-specific membrane antigen (PSMA)-targeted positron emission tomography/computed tomography (PET/CT) in patients with recurrent prostate cancer post-primary radiation therapy. Methods and Materials: A prospective, multi-institutional clinical trial evaluated 2-(3-{1-carboxy-5-[(6-[18F]fluoro-pyridine-3-carbonyl)-amino]-pentyl}-ureido)-pentanedioic acid (18F-DCFPyL) PET/CT restaging in 79 men with recurrent prostate cancer post-primary radiation therapy. We report actual patient management and compare this with proposed management both before and after PSMA-targeted PET/CT. Results: Most patients (59%) had a major change in actual management compared with pre-PET/CT proposed management. The rate of major change was underestimated by immediately post-PET/CT surveys (32%). Eighteen patients with PSMA avidity in the prostate gland suspicious for malignancy had a prostate biopsy. Sensitivity, specificity, and positive predictive values of PSMA uptake in the prostate were 86%, 67%, and 92%, respectively. Thirty percent of patients had directed salvage therapy and 41% underwent systemic therapy. Eleven out of 79 patients (14%) had high-dose-rate brachytherapy alone for local recurrence, and 91% were free of recurrence at a median follow-up of 20 months. Conclusions: Most patients had a major change in actual management compared with pre–PSMA-targeted PET/CT planned management, and this was underestimated by post-PET/CT questionnaires.